Fake or real EU territorialicy? Debating the territorial universe of EU policies - Medeiros, E. (2021)
This paper provides new insights into the main pillars of the territorial universe of EU policies, by undertaking a systematic overview of European Union (EU) key territorial development reports, agendas and programmes. These include the European Spatial Development Perspective (ESDP), the three Territorial Agendas, and the European Territorial Observatory Network (ESPON) reports. The evidence shows widespread territorialicy, understood as a process of incorporating a territorial driven policy design, implementation and evaluation paradigm, still largely dominated by territorial development and territorial cohesion policy rationales. However, the socioeconomic policy prism continues to dominate the design and analysis of EU policies by EU entities.